Coronary angiography and percutaneous coronary intervention after out-of-hospital cardiac arrest: major leaps towards improved survival? - Janssens, Gladys N.; Lemkes, Jorrit S.; van der Hoeven, Nina W.; van Royen, Niels (Journal of Thoracic Disease, 2017)
Out-of-hospital cardiac arrest (OHCA) is a leading cause of death in developed countries. Both resuscitation care and intensive care management for patients after OHCA has notably improved over the years.